Public disorder and globalization - Body-Gendrot, Sophie (Routledge, Taylor & Francis Group, 2017)
Introduction -- Unfolding public disorder and globalization -- Analysing cases of public disorder -- Public disorder as an alternative for change -- The policing of public order -- States and justice -- Terrorism in Paris as an extreme case of global public disorder? -- Conclusion